Match analysis of U9 and U10 English Premier League Academy soccer players using a global positioning system: relevance for talent identification and development - Goto, H.; Morris, J. G.; Nevill, M. E. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to examine the match activity profile of U9 and U10 elite soccer players and to establish if there were any differences between players who were subsequently retained or released by their clubs. Such information should prove valuable in the design of training programs for these very young players and in the talent identification and development process. A Global Positioning System was used to analyze 2-4 interacademy 6-a-side matches of English Premier League Academy players (U9: N = 22 and U10: N = 12) who trained 3 times a week (4.5 hours). Speed zones were created based on 5 and 10-m sprint times, and an independent sample t-test was employed for a statistical analysis. Both squads covered ~4,000 m in total or ~4,700 m/h during a match (p = NS between squads), with the U10 squad tending to cover a greater distance at moderate (p = 0.10) and high speeds (p = 0.08) than the U9 squad. Retained group covered a greater distance than released group (retained vs. released: 4,478 ± 513 m vs. 4,091 ± 462 m, p < 0.05) during a match and covered a greater distance during low-speed running in absolute (1,226 ± 259 m vs. 1,005 ± 221 m, p < 0.05) and relative (1,325 ± 235 m/h vs. 1,132 ± 210 m/h, p < 0.05) terms. Thus, U9 and U10 players cover over 4000 m in match play, and those players who are retained by academies cover a greater distance in total and at low speeds (2.1-3.1 m/s). This information may support the preparation of squad training programs and the talent identification and development process.